Composite and interaction effects in steel‐concrete structures for higher fire resistance - Šapalas, Antanas (Journal of Civil Engineering and Management, 2004)
Wide application of steel structures for office and industrial buildings is one of the main features of Lithuanian and world building industry. This fact is related to an essentially wider use of new structural solutions, new structural members and materials. Usage of different types of materials in one structural system for better utilisation of positive properties of each component is very popular in current building industry. Composite beams, columns, beams‐columns and composite floors can be mentioned. Structures that were designed and erected twenty or more years ago are mostly a collection of different types of structural elements. In general, interaction or composite effect is not taken into account, when designing such structures. Though a considerable number of roofs and ceilings made up of reinforced concrete slabs and steel beams or steel trusses are still in maintenance. Structural solution of the slabs, welding of embedded steel parts of slabs to steel structures, filling with concrete the joints between slabs create the conditions for interaction of slabs and steel structures. The result of this effect is that slabs take up a part of the internal forces of the steel structures and consequently diminish it in steel beams and trusses. It is obvious that this fact leads to the increase of load bearing capacity and fire resistance. The paper deals with the problem of evaluation of composite and structures interaction effect on fire resistance. First Published Online: 14 Oct 2010